Some haematological and biochemical parameters of endangered in snakehead (Channa striatus) - Bakri, Abu Na'im (2012)
A study was carried out to establish reference ranges for haematological and some biochemical variables for the healthy Malaysian Snakehead, Channa striatus. Thirty-seven individuals of the wild Snakehead were procured for the study. For convenience of study, they were grouped into four groups based on weight. Group 1(100g or less), group 2(101-200g), group 3(201-300g), and group 4(300 and above). The ranges of the mean weight, mean length and condition factor (K) for the entire sample were 73.67±11.9-330.00±15.8g, 191.7±10-337.2±16mm and1.37±02-1.64±02K respectively. The range mean values for haematological parameters were 28.67±31-33.67±7.2% for PCV, 26.0±1.0-31.33±6.9% for Haematocrit, 2.88±0.6-3.32±05×10 12 cells/mL for RBC count, 6.33±1.2-7-33±1.5×109 cells/mL for WBC count, 14.11±2.0-17.67±4.1% for Lymphocytes, 21.67±1.5-24.56±3.0% for Monocytes, 14.56±2.9-15.33±1.5% for Eosinophils and 14.78±8.1-21.33±2.9% for Basophils. The ranges of the biochemical variables were 116.72±23.7-124.39±29.2g/l, 34.0±5.0-35.58±5.9g/l, 23.33±2.9-35.32±9.5g/l, 1.03±0.4-1.64±0.8 mmol/L, 14.11±2.0-17.67±4.1 mmol/L and 94.9±38-106.48±18.1 mmol/L for Haemoglobin concentration, Plasma protein, Total protein, Urea concentration, Sodium concentration, and Chloride concentration respectively. The results show significant differences on the weight, length and condition factor (K) among the four groups, but no significant differences between haematological and biochemical parameters.